Functional outcomes of medial open wedge high tibial osteotomy in rural Indian patients with medial compartment osteoarthritis and varus deformity: a prospective study - Sharma, Mukund; Herode, Prafulla; Fiske, Rajendra (International Journal of Research in Orthopaedics, 2025)
Background: Osteoarthritis of the knee is a leading cause of disability in rural India, were cultural practices and delayed presentation often complicate treatment. High tibial osteotomy (HTO) represents a joint-preserving alternative to total knee arthroplasty, particularly suitable for younger patients with medial compartment disease. This study aims to evaluate the functional outcomes of medial open wedge high tibial osteotomy in rural Indian patients with medial compartment osteoarthritis and varus deformity. Methods: This 24-month prospective study at Dr. BVP Rural Medical College, Loni, Maharashtra, evaluated 50 patients with symptomatic medial compartment osteoarthritis undergoing medial open wedge HTO using TomoFix plates. Outcomes were assessed using Visual Analog Scale (VAS), Knee Society Score (KSS) and Knee Society Functional Score (KSFS) over 6-month follow-up. Results: Significant improvements occurred across all measures. Mean VAS improved from 6.7±1.1 to 1.8±0.9 (p<0.001). KSS improved from 54.7±5.8 to 82.8±6.1 (p<0.001) and KSFS from 55.2±4.9 to 83.8±5.7 (p<0.001). Walking distance increased from 178±65 to 575±90 meters (p<0.001). Mechanical axis was corrected from 7.2°±1.3° varus to 2.1°±1.1° valgus. All patients achieved radiological union by 12 weeks. Minor complications occurred in 22% with no major complications. Conclusions: Medial open wedge HTO provides significant functional improvement in rural Indian patients with medial compartment osteoarthritis, offering a cost-effective, culturally appropriate alternative to total knee arthroplasty while preserving traditional sitting postures and occupational activities.